Le potentiel de l'Afrique tropicale en sous-produits utilisables pour l'alimentation du betail - International Livestock Centre for Africa (1979)
Potential of tropical Africa for agro-industrial by-products suitable for animal feeding and fattening w. data on feed value of byproducts from cereals, tubers, oilseeds, sugar canes and others.